Peran Sales Associate Serta Strategi Sales Marketing Dalam Penjualan Produk Charles & Keith Tunjungan Plaza Surabaya - Elfitra Widia Wulandari; Indah Respati Kusumasari (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Kurnia Ciptamoda Gemilang is an Indonesian retail company that was founded in 1998 and currently houses several brands, namely, Charles & Keith, Pedro, Pomelo, and EA7 Emporio Armani in more than 80 stores throughout Indonesia. The purpose of this research is to determine the role of Sales Associates and sales marketing strategies in selling Charles & Keith Tunjungan Plaza Surabaya products. Sales Associates are placed in a position to analyze the operational running of retail activities, both related to Sales and Selling Products, as well as inventory and will also be given the opportunity to interact directly with customers as a Fashion Advisor to be able to provide product information, answer questions and provide suggestions to customers . This research uses a descriptive qualitative approach with in-depth interviews with Sales Associates at the Charles & Keith store Tunjungan Plaza and also personal observations during their internship as a Sales Associate for Charles & Keith Tunjungan Plaza Surabaya. The research results show that the role of the Sales Associate is very crucial in providing a positive customer experience, understanding customer needs, providing accurate product information and also increasing customer transaction value. Apart from that, effective sales marketing strategies are also implemented to increase the level of product sales by using social media, one of which is Value Added Service (Chat Shop), which is a medium for communication, promotion and also online sales via WhatsApp between Sales Associates and customers.